Communicating projects : from Waterfall to Agile - Pilkington, Ann (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"The communication of projects to each stakeholder group is essential to their success. This book is an end-to-end guide for project managers and communication teams seeking to communicate effectively with all constituents, both internal and external. This new edition includes a number of key topical themes that build on the first edition: An introduction to project management for those new to the field, including communicating 'Agile', as many communication practitioners and project managers find themselves having to communicate in an Agile environment, which has a language all of its own. The important role of social media and enterprise social networks as vital communication channels. The principles of change management. The role of storytelling and the importance of translating technical terminology and data into stories that clients and the wider stakeholder groups understand. Crisis communication - ensuring there is a crisis or emergency communication process in place in case it is ever needed. This highly practical book is invaluable reading for communication professionals who are increasingly managing the communication elements of projects. It also supports project managers who need to gain a practical understanding of how to design and deliver communication, as well as helping them to procure effective communication support"--
OCLC-licensed vendor bibliographic record.
Keywords: Project management; Communication in management; BUSINESS & ECONOMICS / Project Management; BUSINESS & ECONOMICS / Industries / Media & Communications Industries; BUSINESS & ECONOMICS / Industrial Management